Additive manufacturing: Toward holistic design. (1st July 2017) - Jared, Bradley H.; Aguilo, Miguel A.; Beghini, Lauren L.; Boyce, Brad L.; Clark, Brett W.; Cook, Adam; Kaehr, Bryan J.; Robbins, Joshua
Abstract: Additive manufacturing offers unprecedented opportunities to design complex structures optimized for performance envelopes inaccessible under conventional manufacturing constraints. Additive processes also promote realization of engineered materials with microstructures and properties that are impossible via traditional synthesis techniques. Enthused by these capabilities, optimization design tools have experienced a recent revival. The current capabilities of additive processes and optimization tools are summarized briefly, while an emerging opportunity is discussed to achieve a holistic design paradigm whereby computational tools are integrated with stochastic process and material awareness to enable the concurrent optimization of design topologies, material constructs and fabrication processes.